Healthcare and Management Strategies for Reducing Maternal Deaths from Obstetric Hemorrhage - Sayfullayevna, Abdullayeva Lola (American Journal of Biomedicine and Pharmacy, 2025)
In connection with the above, the purpose of this study was to study the risk factors leading to the development of massive obstetric hemorrhage. An analysis of 302,000 birth histories in the Samarkand region for the period 2021-2023 was conducted, among which 51 cases of MOH were identified during childbirth and the postpartum period, which amounted to 0.2%. Clinical, laboratory, functional and statistical research methods were used. The article discusses strategies to reduce maternal mortality based on global and local experiences, including training skilled midwives, monitoring reproductive health, providing medical equipment and medicines, and optimizing the health management system. The results of the study have scientific and practical significance in developing prevention and treatment strategies for MMR, formulating health policies, and effectively implementing them in clinical practice.